Double-layer carbon-coated lithium iron phosphate composite material and preparation method and application thereof
By coating the surface of the lithium iron phosphate positive electrode with a double-layer carbon coating, the problem of insufficient wettability in the electrolyte is solved and the rate performance and low-temperature performance of the battery are improved.
Patent Information
- Application Number
- CN202310901949.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-20
- Publication Date
- 2025-01-21
AI Technical Summary
The inability of lithium iron phosphate positive electrode sheets in the electrolyte is insufficient, resulting in the lithium-ion battery being easily transformed into black spots and circulating lithium-ion lithium during the charge and discharge cycle, and the low conductivity affects the battery's rate performance and low temperature performance.
A double-layer carbon-coated lithium iron phosphate composite material is used, and the first carbon coating layer and the second carbon coating layer are coated on the surface of the lithium iron phosphate to improve its conductivity and interfacial wettability of the electrolyte.
It improves the conductivity of lithium iron phosphate and the wettability of electrolyte, and enhances the rate performance and low-temperature performance of lithium-ion batteries.
Smart Images

Figure CN119340353A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a double-layer carbon-coated lithium iron phosphate composite material and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries have been widely used in power tools, electric vehicles and energy storage due to their high voltage platform, high energy density, no memory effect, long cycle life and other advantages. Lithium iron phosphate, as a positive electrode active material for lithium-ion batteries, has excellent safety and cycle performance and is environmentally friendly, and has been a hot topic of development and research in recent years.
[0003] In order to further improve the energy density of lithium-ion batteries, it is necessary to increase the specific capacity and compaction density of lithium iron phosphate. However, the actual specific capacity of lithium iron phosphate is close to the theoretical value, and the improvement is limited. Therefore, increasing the compaction density of lithium iron phosphate has become the main research direction in recent years. However, with the increase in compaction density, the porosity of the positive electrode sheet decreases, resulting in insufficient wettability of the positive electrode sheet in the electrolyte. As the battery charge and discharge cycle proceeds, black spots and cyclic lithium precipitation are prone to occur. In addition, the low conductivity of lithium iron phosphate will affect the mass transfer impedance inside the battery, resulting in a decrease in the battery's rate performance and low-temperature performance. Summary of the invention
[0004] The present application provides a double-layer carbon-coated lithium iron phosphate composite material and a preparation method thereof, which improves the conductivity of lithium iron phosphate and its wettability in an electrolyte, and improves the rate performance and low-temperature performance of a battery.
[0005] The present application also provides an application of the above double-layer carbon-coated lithium iron phosphate composite material.
[0006] In a first aspect, the present application provides a double-layer carbon-coated lithium iron phosphate composite material, the composite material comprising lithium iron phosphate and a carbon coating layer coated on the surface of the lithium iron phosphate, the carbon coating layer comprising a first carbon coating layer and a second carbon coating layer, the first carbon coating layer being coated on the surface of the lithium iron phosphate, and the second carbon coating layer being coated on the surface of the first carbon coating layer away from the lithium iron phosphate, wherein:
[0007] The first carbon coating layer D / I G Less than the I of the second carbon coating layer D / I G , I D / I G It refers to the peak intensity ratio of the D peak and the G peak in the Raman spectra of the first carbon coating layer and the second carbon coating layer.
[0008] In a possible implementation, the lithium iron phosphate composite material coated with the first carbon coating layer isD / I G 0.7~0.95;
[0009] And / or, a lithium iron phosphate composite material coated with a first carbon coating layer and a second carbon coating layer D / I G It is 1.0~1.3.
[0010] In a possible implementation, the lithium iron phosphate composite material coated with the first carbon coating layer is D / I G I1, I of the lithium iron phosphate composite material coated with the first carbon coating layer and the second carbon coating layer D / I G The mass of the first carbon coating layer accounts for C1% of the total mass of the double-layer carbon-coated lithium iron phosphate composite material, the mass of the second carbon coating layer accounts for C2% of the double-layer carbon-coated lithium iron phosphate composite material, and (I1*C1) / (I2*C2)≥1.5.
[0011] In a possible implementation manner, the mass ratio of the first carbon coating layer to the second carbon coating layer is 1:(0.2-0.5).
[0012] In a possible implementation, the mass of the carbon coating layer accounts for a percentage of M1% of the total mass of the lithium iron phosphate composite material, the number of carbon layers of the first carbon coating layer is L1, the thickness of the first carbon coating layer is D1, the thickness of the second carbon coating layer is D2, M1 / (L1 2 *D1*D2)≥0.0013.
[0013] In a possible implementation, the percentage M1% of the mass of the carbon coating layer to the total mass of the lithium iron phosphate composite material is 1.0% to 3.0%.
[0014] In a possible implementation manner, the number of carbon layers L1 of the first carbon coating layer is 2 to 20 layers.
[0015] In a possible implementation, the thickness D1 of the first carbon coating layer is 1-15 nm.
[0016] In a possible implementation manner, the thickness D2 of the second carbon coating layer is 1-15 nm.
[0017] The second aspect of the present application provides a method for preparing any of the above-mentioned lithium iron phosphate composite materials, comprising the following steps:
[0018] Dispersing a lithium source, a phosphorus source, and an iron source in a solvent and performing ball milling to obtain a first dispersed slurry;
[0019] The first dispersed slurry is spray-dried, and the obtained first solid particles are subjected to a first sintering treatment; during the first sintering treatment, a first carbon source is introduced to perform chemical vapor deposition to obtain lithium iron phosphate coated with a first carbon coating layer;
[0020] Dispersing lithium iron phosphate coated with a first carbon coating layer and a second carbon source in a solvent, and mixing them evenly to obtain a second dispersed slurry;
[0021] The second dispersed slurry is spray-dried, and the obtained second solid particles are subjected to a second sintering treatment to obtain a double-layer carbon-coated lithium iron phosphate composite material.
[0022] In a possible implementation, the temperature of the first sintering treatment is 500-900° C., and the time is 3-20 hours;
[0023] And / or, the temperature of the second sintering treatment is 300-700° C., and the time is 2-15 hours.
[0024] A third aspect of the present application provides a pole piece, comprising any of the above-mentioned double-layer carbon-coated lithium iron phosphate composite materials.
[0025] A fourth aspect of the present application provides a lithium-ion battery, comprising the above-mentioned pole piece.
[0026] A fifth aspect of the present application provides an electronic device, wherein a driving source or an energy storage source of the electronic device includes the above-mentioned lithium-ion battery.
[0027] The present application provides a double-layer carbon-coated lithium iron phosphate composite material, comprising lithium iron phosphate and a first carbon coating layer and a second carbon coating layer sequentially coated on the surface of the lithium iron phosphate, wherein the graphitization degree of the first carbon coating layer is higher than that of the second carbon coating layer, which helps to improve the conductivity of the lithium iron phosphate, and the second carbon coating layer includes amorphous carbon, which has rich organic functional groups that can effectively improve the interface wettability between the electrolyte and the lithium iron phosphate. Therefore, the double-layer carbon-coated lithium iron phosphate composite material provided by the present application helps to improve the rate performance and low temperature performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the implementation methods in the embodiments of the present application or the related technologies, the following is a brief introduction to the drawings required for use in the embodiments or the related technology descriptions. Obviously, the drawings described below are some embodiments of the present application, and a person skilled in the art can also obtain other drawings based on these drawings.
[0029] Figure 1 This is an observation image of the lithium iron phosphate composite material provided in Example 1 of the present application under a transmission electron microscope;
[0030] Figure 2 This is an observation image of the lithium iron phosphate composite material provided in Comparative Example 1 of the present application under a transmission electron microscope. DETAILED DESCRIPTION
[0031] The terms used in the implementation section of this application are only used to explain the specific embodiments of this application and are not intended to limit this application.
[0032] To facilitate understanding, the relevant technical terms involved in the embodiments of the present application are first explained and illustrated.
[0033] Rechargeable battery: also known as rechargeable battery or storage battery, refers to a battery that can be recharged to activate the active material after the battery is discharged and continue to be used.
[0034] Lithium-ion battery: A type of secondary battery that mainly relies on the movement of lithium ions between the positive electrode and the negative electrode to work. During the charge and discharge process, Li+ is embedded and de-embedded between the two electrodes: during charging, Li+ is de-embedded from the positive electrode and embedded in the negative electrode through the electrolyte, and the negative electrode is in a lithium-rich state; the opposite is true during discharge.
[0035] Positive electrode (cathode): In the primary battery, the electrode from which the current flows has a higher potential and is the positive electrode. It gains electrons for reduction. In the electrolytic cell, the positive electrode is the electrode connected to the positive pole of the power supply and loses electrons for oxidation.
[0036] Anode: The anode is the end of the power source with a lower potential. In a primary cell, it refers to the electrode that performs oxidation, and in an electrolytic cell, it refers to the electrode that performs reduction.
[0037] Electrolyte: The medium that provides ion exchange between the positive and negative electrodes of a battery.
[0038] Battery separator: refers to a layer of separator material between the positive and negative electrodes of the battery. Its main function is to isolate the positive and negative electrodes and prevent electrons in the battery from passing freely, while allowing ions to pass freely between the positive and negative electrodes.
[0039] As an energy storage device, lithium-ion batteries include positive electrode plates, separators, negative electrode plates and electrolytes. The positive electrode plates include positive current collectors and positive active material layers arranged on the surface of the positive current collectors. The negative electrode plates include negative current collectors and negative active material layers arranged on the surface of the negative current collectors. The positive active material layers and negative active material layers include positive active materials and negative active materials respectively. The separator is located between the positive electrode plates and the negative electrode plates to prevent the two from contacting and causing a short circuit. During the charging process of lithium-ion batteries, lithium ions are released from the positive active material, and are embedded in the negative active material after passing through the electrolyte and the separator. During the discharging process of lithium-ion batteries, lithium ions are released from the negative active material, and are embedded in the positive active material after passing through the electrolyte and the separator.
[0040] Lithium iron phosphate, as the positive electrode active material for lithium-ion batteries, has the chemical formula LiFePO4. It has been a hot topic of development and research in recent years because its raw materials are simple and safe, does not contain heavy metal elements such as cobalt, is environmentally friendly, and lithium-ion batteries including lithium iron phosphate have high safety and long cycle life.
[0041] Energy density is the capacity that can be stored in a unit volume of lithium-ion batteries. As the requirements for the energy density of lithium-ion batteries become higher and higher, increasing the compaction density is one of the means to increase the energy density of lithium-ion batteries. The compaction density refers to the surface density of the pole piece / (the thickness of the pole piece after rolling-the thickness of the current collector) in the design process of lithium-ion batteries. It can be understood that with the increase of compaction density, the more lithium iron phosphate can be accommodated in a unit volume of the positive electrode plate, and the larger the capacity of the lithium-ion battery. However, with the increase of compaction density, the degree of extrusion between the lithium iron phosphate particles becomes greater, and the porosity of the positive electrode plate becomes less, resulting in insufficient wettability of the positive electrode plate in the electrolyte. As the lithium-ion battery is charged and discharged, lithium ions cannot enter the negative electrode active material, and black spots and cyclic lithium precipitation are likely to occur. In addition, the insufficient conductivity of lithium iron phosphate will affect the mass transfer impedance inside the battery, resulting in a decrease in the battery's rate performance and low-temperature performance.
[0042] In order to solve the above technical problems, the first aspect of the embodiment of the present application provides a double-layer carbon-coated lithium iron phosphate composite material, which includes lithium iron phosphate and a carbon coating layer coated on the surface of the lithium iron phosphate, wherein the carbon coating layer includes a first carbon coating layer and a second carbon coating layer, wherein the first carbon coating layer is coated on the surface of the lithium iron phosphate, and the second carbon coating layer is coated on the surface of the first carbon coating layer away from the lithium iron phosphate, wherein:
[0043] The first carbon coating layer D / I G Less than the I of the second carbon coating layer D / I G , I D / IG It refers to the peak intensity ratio of the D peak and the G peak in the Raman spectra of the first carbon coating layer and the second carbon coating layer.
[0044] The lithium iron phosphate composite material provided in the embodiment of the present application is a core-shell structure, wherein the core is lithium iron phosphate, and the shell is a double-layer carbon coating layer. The carbon coating layer close to the lithium iron phosphate side is the first carbon coating layer, and the carbon coating layer away from the lithium iron phosphate side is the second carbon coating layer. The first carbon coating layer has a distinct layered structure and a high degree of graphitization, and thus has good conductivity. The second coating layer is amorphous carbon / low degree of graphitization, and has rich organic functional groups on its surface. On the basis of ensuring the overall conductivity of the lithium iron phosphate composite material, it can reduce the infiltration time of the electrolyte, thereby improving the wettability of the electrolyte.
[0045] This application uses I D / I G Characterize the graphitization degree of the first carbon coating layer and the second carbon coating layer, specifically, I D / I G It refers to the peak intensity ratio of the D peak and the G peak in the Raman spectra of the first carbon coating layer and the second carbon coating layer. Both the D peak and the G peak are Raman characteristic peaks of carbon atomic crystals, with peaks at 1300 cm -1 and 1580cm -1 Nearby, the D peak represents the defects of the carbon atom crystal, and the G peak represents the in-plane stretching vibration of the sp2 hybridization of the carbon atom. The peak intensity ratio of the D peak and the G peak can reflect the degree of graphitization of the carbon layer.
[0046] The first carbon coating layer and the second carbon coating layer D / I G The qualitative judgment can be made by the following method. Specifically, according to the Raman spectrum of the lithium iron phosphate material coated with only the first coating layer, the peak intensity ratio I of the D peak and the G peak is obtained. D / I G , denoted as I1, and the peak intensity ratio of the D peak to the G peak is obtained according to the Raman spectrum of the lithium iron phosphate particles including the double-layer carbon coating layer. D / I G , denoted as I2. When I2>I1, it indicates that the introduction of the second carbon coating layer increases the defects of the carbon atom crystal, indicating that the I D / I G Greater than the I of the first carbon coating layer D / I G .
[0047] In a specific embodiment, the lithium iron phosphate composite material coated with the first carbon coating layer is D / I GThe molecular weight of the present invention is 0.7 to 0.95, and specifically can be 0.7, 0.72, 0.75, 0.78, 0.80, 0.82, 0.85, 0.88, 0.90, 0.92, 0.95 or a range consisting of any two thereof.
[0048] In a specific embodiment, the lithium iron phosphate composite material coated with the first carbon coating layer and the second carbon coating layer is D / I G The value is 1.0 to 1.3, and specifically can be 1.00, 1.02, 1.05, 1.08, 1.10, 1.12, 1.15, 1.18, 1.20, 1.22, 1.25, 1.28, 1.30 or any two thereof. D / I G The larger the value, the worse the conductivity of the lithium iron phosphate composite material. D / I G When it is greater than 1.3, it is not conducive to improving the conductivity of the lithium iron phosphate composite material.
[0049] In a specific embodiment, the lithium iron phosphate composite material coated with the first carbon coating layer is D / I G I1, I of the lithium iron phosphate composite material coated with the first carbon coating layer and the second carbon coating layer D / I G The mass of the first carbon coating layer accounts for C1% of the total mass of the double-layer carbon-coated lithium iron phosphate composite material, and the mass of the second carbon coating layer accounts for C2% of the double-layer carbon-coated lithium iron phosphate composite material, (I1*C1) / (I2*C2)≥1.5. When the test data of the lithium iron phosphate composite material meets the above relationship, it indicates that the proportion of the first carbon coating layer in the carbon coating layer is relatively high, and the more graphitized carbon content, the more conducive to further improve the conductivity of the lithium iron phosphate composite material, improve the rate performance and low temperature performance of the lithium ion battery, and the second carbon coating layer mainly improves the wettability of the electrolyte to it through the organic functional groups on its surface. Therefore, its carbon content has no obvious effect on the improvement of the electrolyte wettability.
[0050] Furthermore, (I1*C1) / (I2*C2)≥1.8, for example, (I1*C1) / (I2*C2) is 1.8, 1.85, 1.90, 1.95, 2.0, 2.05, 2.10, 2.15, 2.20, 2.25, 2.30, 2.35, 2.40, 2.45, 2.50, 2.55, 2.60, 2.65, 2.6, 2.65, 2.70, 2.75, 2.80, 2.85, 2.90, 2.95, 3.0, etc.
[0051] In a specific embodiment, the mass ratio of the first carbon coating layer to the second carbon coating layer is 1:(0.2-0.5), specifically 1:0.2, 1:0.25, 1:0.30, 1:0.35, 1:0.40, 1:0.45, 1:0.50 or within the range of any two thereof.
[0052] In a specific embodiment, the mass of the carbon coating layer accounts for a percentage of the total mass of the lithium iron phosphate composite material of M1%, the number of carbon layers of the first carbon coating layer is L1, the thickness of the first carbon coating layer is D1, the thickness of the second carbon coating layer is D2, M1 / (L1 2 *D1*D2)≥0.0013, for example, M1 / (L1 2 *D1*D2) is 0.0013, 0.0015, 0.002, 0.0025, 0.0030, 0.0035, 0.0040, 0.0045, 0.0050, 0.0055, 0.0060, 0.0065, 0.0070, 0.0075, 0.0080, 0.0085, 0.0090, 0.0095, 0.010, etc. When the test data of the lithium iron phosphate composite material meets the relationship range, it is helpful to take into account the carbon content and the number of layers of the first carbon coating layer. When the carbon content is constant, as the number of layers of the first carbon coating layer decreases, it is helpful to improve the interface diffusion efficiency of lithium ions.
[0053] In a specific embodiment, the mass of the carbon coating layer accounts for a percentage M1% of the total mass of the lithium iron phosphate composite material of 1.0% to 3.0%, specifically 1.0%, 1.2%, 1.5%, 1.8%, 2.0%, 2.2%, 2.5%, 2.8%, 3.0% or any two thereof. When the mass of the carbon coating layer is less than 1.0%, the improvement of the conductivity and electrolyte wettability of the lithium iron phosphate is not obvious, and when it is higher than 3.0%, the specific surface area of the lithium iron phosphate composite material increases significantly, which is not conducive to the processing performance.
[0054] In a specific embodiment, the first carbon coating layer has a distinct layered structure, and the number of carbon layers L1 of the first carbon coating layer is 2 to 20 layers, specifically 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20 layers, etc. When the number of carbon layers of the first coating layer exceeds 20 layers, the carbon content will be too high, the specific surface area of the lithium iron phosphate composite material will be increased, and the interface diffusion efficiency of lithium ions will be hindered. The number of carbon layers of the first carbon coating layer can be observed and statistically obtained by TEM.
[0055] Furthermore, the number of carbon layers L1 in the first carbon coating layer is 4 to 8 layers.
[0056] In a specific embodiment, the thickness D1 of the first carbon coating layer is 1-15 nm, specifically 1 nm, 2 nm, 3 nm, 5 nm, 8 nm, 10 nm, 12 nm, 13 nm, 15 nm or a range consisting of any two thereof.
[0057] In a specific embodiment, the thickness D2 of the second carbon coating layer is 1-15 nm, specifically 1 nm, 2 nm, 3 nm, 5 nm, 8 nm, 10 nm, 12 nm, 13 nm, 15 nm or a range consisting of any two thereof.
[0058] It can be understood that the thickness of the first carbon coating layer refers to the average value of the distance between the surface of the lithium iron phosphate core particle and the outer surface of the first carbon coating away from the lithium iron phosphate particle, and the thickness of the second carbon coating layer refers to the average value of the distance between the first carbon coating layer and the outer surface of the second carbon coating layer away from the lithium iron phosphate particle, which can be observed and statistically obtained through TEM.
[0059] In a specific embodiment, the surface of the second carbon coating layer includes a plurality of organic functional groups, such as organic functional groups containing at least one element of N, C, O, and S, and the mass of the organic functional groups is 10% to 50% of the mass of the second carbon coating layer.
[0060] In summary, the present application provides a double-layer carbon-coated lithium iron phosphate composite material, including lithium iron phosphate and a first carbon coating layer and a second carbon coating layer sequentially coated on the surface of the lithium iron phosphate, and the graphitization degree of the first carbon coating layer is higher than that of the second carbon coating layer, which helps to improve the conductivity of the lithium iron phosphate, and the second carbon coating layer includes amorphous carbon, which has rich organic functional groups that can effectively improve the interface wettability between the electrolyte and the lithium iron phosphate. Therefore, the double-layer carbon-coated lithium iron phosphate composite material provided by the present application helps to improve the rate performance and low temperature performance of the battery.
[0061] A second aspect of the present application provides a method for preparing any of the above-mentioned lithium iron phosphate composite materials, comprising the following steps:
[0062] Dispersing a lithium source, a phosphorus source, and an iron source in a solvent and performing ball milling to obtain a first dispersed slurry;
[0063] The first dispersed slurry is spray-dried, and the obtained first solid particles are subjected to a first sintering treatment; during the first sintering treatment, a first carbon source is introduced to perform chemical vapor deposition to obtain lithium iron phosphate coated with a first carbon coating layer;
[0064] Dispersing lithium iron phosphate coated with a first carbon coating layer and a second carbon source in a solvent, and mixing them evenly to obtain a second dispersed slurry;
[0065] The second dispersed slurry is spray-dried, and the obtained second solid particles are subjected to a second sintering treatment to obtain a double-layer carbon-coated lithium iron phosphate composite material.
[0066] The preparation method is described in detail below:
[0067] Step 1, dispersing a lithium source, a phosphorus source, and an iron source in a solvent and performing ball milling to obtain a first dispersed slurry;
[0068] The present application does not impose any further restrictions on the types of lithium source, phosphorus source, and iron source, which may be conventional materials in the art. For example, the lithium source is selected from one or more of lithium oxide, lithium hydroxide, lithium carbonate, lithium acetate, lithium nitrate, lithium phosphate, and lithium dihydrogen phosphate; the phosphorus source is selected from one or more of phosphorus pentoxide, phosphoric acid, ferric phosphate, diammonium phosphate, diammonium hydrogen phosphate, ammonium ferrous phosphate, and ammonium hydrogen phosphate; the iron source is selected from one or more of iron, ferrous oxide, ferrous oxide, ferrous trioxide, ferrous sulfate, ammonium ferrous sulfate, ferric phosphate, ferrous phosphate, ammonium ferrous phosphate, ferrous citrate, and ferrous oxalate.
[0069] The specific compounds of the lithium source, phosphorus source and iron source are mixed with a solvent in a certain ratio and ball-milled. The solvent can be water. The ball-milling time is 2 to 10 hours. After the ball-milling, a uniformly dispersed first dispersed slurry is obtained.
[0070] Step 2, spray drying the first dispersed slurry, and performing a first sintering treatment on the obtained first solid particles; during the first sintering treatment, introducing a first carbon source, performing chemical vapor deposition, and obtaining lithium iron phosphate coated with a first carbon coating layer;
[0071] The first dispersed slurry obtained in step 1 is spray dried by conventional technical means in the art to obtain first solid particles after removing the solvent; the spray drying can be carried out in a pressure spray dryer, a centrifugal spray dryer or an airflow spray dryer.
[0072] Subsequently, the first solid particles are subjected to a first sintering treatment, and at the same time, a first carbon source is introduced to coat the surface of the lithium iron phosphate with a first carbon coating layer by chemical vapor deposition.
[0073] Specifically, the first sintering treatment can be carried out in a high-temperature heating device such as a tubular furnace, a muffle furnace, a box furnace, a roller kiln, a push plate kiln, or a rotary kiln. During the sintering process, the first solid particles are placed in the high-temperature heating device. At the same time, a first carbon source is introduced into the high-temperature heating device. The first carbon source is selected from one or more of methane, ethylene, acetylene, propylene, CO, and benzene. In an inert gas atmosphere, the sintering temperature is increased to 500-900°C. Under the action of high temperature, the carbon atoms in the first carbon source undergo physical changes to form a first carbon coating layer having an obvious layered structure and a high degree of graphitization. After sintering for 3-20 hours, a lithium iron phosphate composite material coated with the first carbon coating layer is obtained.
[0074] Furthermore, the inert gas is selected from one or more of nitrogen and argon.
[0075] The amount of the first carbon source introduced can be determined according to the content of the first carbon coating layer, and the introduction rate is generally controlled at 1.0 to 6.0 m / s. 3 / h, which helps to obtain the first carbon coating layer with a corresponding number of layers.
[0076] Step 3, dispersing the lithium iron phosphate coated with the first carbon coating layer and the second carbon source in a solvent, and mixing them evenly to obtain a second dispersed slurry;
[0077] Based on the lithium iron phosphate coated with the first carbon coating layer obtained in step 2, the lithium iron phosphate is mixed with a second carbon source and dispersed in a solvent, and a second dispersed slurry is obtained after mixing evenly.
[0078] Furthermore, the second carbon source can be one or more of glucose, PEG, sucrose, starch, citric acid, polypropylene, and polyols. The mass of the second carbon source can be determined according to the content of the second carbon coating layer.
[0079] Furthermore, the solvent may be water.
[0080] Step 4, spray drying the second dispersed slurry, and performing a second sintering treatment on the obtained second solid particles to obtain a double-layer carbon-coated lithium iron phosphate composite material;
[0081] The second dispersed slurry is spray-dried using the same spray-drying method as in step 2 to obtain second solid particles.
[0082] Subsequently, the second solid particles are subjected to a second sintering treatment in an inert gas atmosphere. The temperature of the second sintering treatment is 300-700° C., and the sintering time is 2-15 hours. After the sintering, a double-layer carbon-coated lithium iron phosphate composite material is obtained.
[0083] It is understandable that after the first sintering treatment and the second sintering treatment, the sintered product can be crushed to obtain a lithium iron phosphate composite material that meets the particle size requirements. This can be done specifically according to conventional technical means in the field, and this application will not elaborate on this.
[0084] A third aspect of an embodiment of the present application provides a pole piece, which includes the double-layer carbon-coated lithium iron phosphate composite material provided in the first aspect.
[0085] Based on the double-layer carbon-coated lithium iron phosphate composite material provided in the first aspect of the present application, the pole piece provided in the present application can not only ensure the compaction density, but also has good conductivity and electrolyte wettability, which helps to improve the rate performance and low temperature performance of the lithium-ion battery.
[0086] In a specific embodiment, the electrode sheet provided in the embodiment of the present application is a positive electrode sheet, including a positive electrode collector and a positive electrode active material layer arranged on the surface of the positive electrode collector. The positive electrode collector is usually a metal foil, such as aluminum foil, and the positive electrode active material layer includes the aforementioned double-layer carbon-coated lithium iron phosphate composite material, a conductive agent and a binder.
[0087] The types of conductive agent and binder can be selected according to conventional technical means in the art. For example, the conductive agent is selected from one or more of conductive carbon black, acetylene black, Ketjen black, conductive graphite, conductive carbon fiber, carbon nanotubes, single-walled carbon nanotubes, multi-arm carbon nanotubes, and carbon fibers; the binder is selected from one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), and polyethylene oxide (PEO); and the solvent can be N-methylpyrrolidone (NMP).
[0088] The ratio of the double-layer carbon-coated lithium iron phosphate composite material, the conductive agent and the binder can be set according to actual needs. According to the conventional positive electrode sheet preparation method in the art, the aforementioned double-layer carbon-coated lithium iron phosphate composite material, the conductive agent and the binder are added to the solvent and stirred and dispersed to obtain a positive electrode active material slurry, and then the positive electrode active material slurry is coated on the surface of the positive electrode collector, and the positive electrode sheet is obtained after rolling.
[0089] A fourth aspect of an embodiment of the present application provides a lithium-ion battery, which includes the electrode provided by the third aspect.
[0090] Based on the performance of the positive electrode plate provided in the third aspect of the present application, a lithium-ion battery including the plate has good rate performance and low temperature performance.
[0091] In a specific embodiment, the lithium-ion battery also includes a negative electrode plate, a separator and an electrolyte, wherein the negative electrode plate includes a negative electrode current collector and a negative electrode active material layer arranged on the surface of the negative electrode current collector, the negative electrode active material layer includes a negative electrode active material, a conductive agent and a binder, the negative electrode active material can be selected from one or more of silicon, silicon carbon, artificial graphite, natural graphite, hard carbon, soft carbon, and intermediate phase carbon microspheres, and the selection of the conductive agent and the binder is the same as the positive electrode plate.
[0092] The diaphragm and the electrolyte are both conventional materials in the art. For example, the diaphragm can be selected from one or more of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The electrolyte includes at least an organic solvent and a lithium salt, wherein the organic solvent can be selected from one or more of ethylene carbonate, butylene carbonate, propylene carbonate, ethyl methyl carbonate, vinylene carbonate, vinyl ethylene carbonate, fluoroethylene carbonate, ethyl methyl carbonate, difluoroethylene carbonate, fluorodimethyl carbonate, dimethyl carbonate, diethyl carbonate, and dipropyl carbonate; the lithium salt can be selected from one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium bistrifluoromethylsulfonyl imide (LiTFSI), and lithium bisfluorosulfonyl imide (LiFSI).
[0093] A fifth aspect of the embodiments of the present application provides an electronic device, wherein a driving source or an energy storage unit of the electronic device is the lithium-ion battery of the fourth aspect described above.
[0094] In a specific implementation, the electronic device may include, but is not limited to, energy storage equipment used in communication base stations, photovoltaics, industry and commerce, and other fields.
[0095] Hereinafter, the double-layer carbon-coated lithium iron phosphate composite material and the lithium ion battery provided in the embodiments of the present application are introduced in detail through specific examples.
[0096] Example 1
[0097] This embodiment provides a method for preparing a double-layer carbon-coated lithium iron phosphate composite material, comprising the following steps:
[0098] Step 1, dispersing lithium carbonate and iron phosphate in water and ball milling, and obtaining a first dispersed slurry after ball milling for 6 hours;
[0099] Step 2, spray drying the first dispersed slurry at a spray drying temperature of 280° C. to obtain first solid particles;
[0100] The first solid particles were subjected to a first sintering treatment in a nitrogen atmosphere. 3 Ethylene gas was introduced at a rate of / h, the temperature in the furnace was controlled to be 700°C, and lithium iron phosphate coated with the first carbon coating layer was obtained after sintering for 3h; Raman test was performed on the lithium iron phosphate coated with the first carbon coating layer, and ID / I G is 0.93;
[0101] Step 3, crushing the lithium iron phosphate coated with the first carbon coating layer, mixing the crushed lithium iron phosphate coated with the first carbon coating layer with glucose and dispersing them in water, and stirring for 1 hour to obtain a second dispersed slurry;
[0102] Step 4, spray drying the second dispersed slurry at a spray drying temperature of 200° C. to obtain second solid particles;
[0103] Step 5: Under a nitrogen atmosphere, the obtained second solid particles are subjected to a second sintering treatment at a sintering temperature of 600° C. for a sintering time of 2 h. After the sintering is completed, a double-layer carbon-coated lithium iron phosphate composite material is obtained.
[0104] The obtained double-layer carbon-coated lithium iron phosphate composite material was placed under a transmission electron microscope for observation. Figure 1 As shown, it can be seen that the surface of lithium iron phosphate is sequentially coated with a first carbon coating layer and a second carbon coating layer, and the degree of graphitization of the first carbon coating layer is significantly higher than that of the second carbon coating layer; and, according to transmission electron microscopy observation, the thickness D1 of the first carbon coating layer is 3 nm, and the thickness D2 of the second carbon coating layer is 7 nm.
[0105] The obtained double-layer carbon-coated lithium iron phosphate composite material was subjected to Raman testing, and the results were as follows: D / I G is 1.2.
[0106] The carbon content of the composite material prepared in steps 2 and 5 was tested, and it was found that the total mass of the carbon coating layer was 1.5% of the mass of the double-layer carbon-coated lithium iron phosphate composite material, wherein the mass of the first carbon coating layer accounted for 1.1% of the total mass of the double-layer carbon-coated lithium iron phosphate composite material, and the mass of the second carbon coating layer accounted for 0.4% of the total mass of the double-layer carbon-coated lithium iron phosphate composite material.
[0107] The value calculated according to (I1*C1) / (I2*C2) is (0.93*1.1) / (1.2*0.4)=2.13.
[0108] According to the TEM electron microscope observation results, the number of carbon layers in the first carbon coating layer is 6.
[0109] According to M1 / (L1 2 *D1*D2) is calculated to be 1.5 / (6 2 *3*7)=0.0020.
[0110] Example 2
[0111] This embodiment provides a method for preparing a double-layer carbon-coated lithium iron phosphate composite material, comprising the following steps:
[0112] Step 1, dispersing lithium carbonate and iron phosphate in water and ball milling them to obtain a first dispersed slurry after ball milling for 4 hours;
[0113] Step 2, spray drying the first dispersed slurry at a spray drying temperature of 200° C. to obtain first solid particles;
[0114] The first solid particles were subjected to a first sintering treatment in a nitrogen atmosphere. 3 Acetylene gas was introduced at a rate of / h, the temperature in the furnace was controlled to be 720°C, and lithium iron phosphate coated with the first carbon coating layer was obtained after sintering for 3h; Raman test was performed on the lithium iron phosphate coated with the first carbon coating layer, and I D / I G is 0.85;
[0115] Step 3, crushing the lithium iron phosphate coated with the first carbon coating layer, mixing the crushed lithium iron phosphate coated with the first carbon coating layer with PEG and sucrose and dispersing them in water, and stirring for 2 hours to obtain a second dispersed slurry;
[0116] Step 4, spray drying the second dispersed slurry at a spray drying temperature of 200° C. to obtain second solid particles;
[0117] Step 5: Under a nitrogen atmosphere, the obtained second solid particles are subjected to a second sintering treatment at a sintering temperature of 550° C. for 3 hours. After the sintering is completed, a double-layer carbon-coated lithium iron phosphate composite material is obtained.
[0118] The obtained double-layer carbon-coated lithium iron phosphate composite material was placed under a transmission electron microscope for observation. It can be seen that the surface of the lithium iron phosphate is sequentially coated with a first carbon coating layer and a second carbon coating layer, and the degree of graphitization of the first carbon coating layer is significantly higher than that of the second carbon coating layer; and, according to transmission electron microscope observation, the thickness D1 of the first carbon coating layer is 2nm, and the thickness D2 of the second carbon coating layer is 4nm.
[0119] The obtained double-layer carbon-coated lithium iron phosphate composite material was subjected to Raman testing, and the obtained I D / I G is 1.16.
[0120] The carbon content of the composite material prepared in steps 2 and 5 was tested, and it was found that the total mass of the carbon coating layer was 1.4% of the mass of the double-layer carbon-coated lithium iron phosphate composite material, wherein the mass of the first carbon coating layer accounted for 1.1% of the total mass of the double-layer carbon-coated lithium iron phosphate composite material, and the mass of the second carbon coating layer accounted for 0.3% of the total mass of the double-layer carbon-coated lithium iron phosphate composite material.
[0121] The value calculated according to (I1*C1) / (I2*C2) is (0.85*1.1) / (1.16*0.3)=2.68.
[0122] According to the TEM electron microscope observation results, there are 5 layers in the first carbon coating layer.
[0123] According to M1 / (L1 2 *D1*D2) is calculated to be 1.4 / (5 2 *2*4)=0.007.
[0124] Example 3
[0125] This embodiment provides a method for preparing a double-layer carbon-coated lithium iron phosphate composite material, comprising the following steps:
[0126] Step 1, dispersing lithium carbonate and iron phosphate in water and ball milling them to obtain a first dispersed slurry after ball milling for 4 hours;
[0127] Step 2, spray drying the first dispersed slurry at a spray drying temperature of 280° C. to obtain first solid particles;
[0128] The first solid particles are subjected to a first sintering treatment in a nitrogen atmosphere. 3 / h, acetylene gas was introduced, the temperature in the furnace was controlled to be 600°C, and lithium iron phosphate coated with the first carbon coating layer was obtained after sintering for 2h; Raman test was performed on the lithium iron phosphate coated with the first carbon coating layer, and I D / I G is 0.9;
[0129] Step 3, crushing the lithium iron phosphate coated with the first carbon coating layer, mixing the crushed lithium iron phosphate coated with the first carbon coating layer with sucrose and dispersing them in water, and stirring for 2 hours to obtain a second dispersed slurry;
[0130] Step 4, spray drying the second dispersed slurry at a spray drying temperature of 280° C. to obtain second solid particles;
[0131] Step 5: Under a nitrogen atmosphere, the obtained second solid particles are subjected to a second sintering treatment at a sintering temperature of 500° C. for 10 h. After the sintering is completed, a double-layer carbon-coated lithium iron phosphate composite material is obtained.
[0132] The obtained double-layer carbon-coated lithium iron phosphate composite material was placed under a transmission electron microscope for observation. It can be seen that the surface of the lithium iron phosphate is sequentially coated with a first carbon coating layer and a second carbon coating layer, and the degree of graphitization of the first carbon coating layer is significantly higher than that of the second carbon coating layer; and, according to transmission electron microscope observation, the thickness D1 of the first carbon coating layer is 5nm, and the thickness D2 of the second carbon coating layer is 6nm.
[0133] The obtained double-layer carbon-coated lithium iron phosphate composite material was subjected to Raman testing, and the obtained I D / I G is 1.22.
[0134] The carbon content of the composite material prepared in steps 2 and 5 was tested, and it was found that the total mass of the carbon coating layer was 1.3% of the mass of the double-layer carbon-coated lithium iron phosphate composite material, wherein the mass of the first carbon coating layer accounted for 0.6% of the total mass of the double-layer carbon-coated lithium iron phosphate composite material, and the mass of the second carbon coating layer accounted for 0.7% of the total mass of the double-layer carbon-coated lithium iron phosphate composite material.
[0135] The value calculated according to (I1*C1) / (I2*C2) is (0.9*0.6) / (1.22*0.7)=0.63.
[0136] According to the TEM electron microscope observation results, there are 6 layers in the first carbon coating layer.
[0137] According to M1 / (L1 2 *D1*D2) is calculated to be 1.3 / (6 2 *5*6)=0.0012.
[0138] Example 4
[0139] This embodiment provides a method for preparing a double-layer carbon-coated lithium iron phosphate composite material, comprising the following steps:
[0140] Step 1, dispersing lithium carbonate and iron phosphate in water and ball milling them to obtain a first dispersed slurry after ball milling for 4 hours;
[0141] Step 2, spray drying the first dispersed slurry at a spray drying temperature of 250° C. to obtain first solid particles;
[0142] The first solid particles were subjected to a first sintering treatment in a nitrogen atmosphere. 3Methane gas was introduced at a rate of / h, the temperature in the furnace was controlled to be 700°C, and lithium iron phosphate coated with the first carbon coating layer was obtained after sintering for 3h; Raman test was performed on the lithium iron phosphate coated with the first carbon coating layer, and I D / I G is 0.95;
[0143] Step 3, crushing the lithium iron phosphate coated with the first carbon coating layer, mixing the crushed lithium iron phosphate coated with the first carbon coating layer with sucrose and dispersing them in water, and stirring for 2 hours to obtain a second dispersed slurry;
[0144] Step 4, spray drying the second dispersed slurry at a spray drying temperature of 200° C. to obtain second solid particles;
[0145] Step 5: Under a nitrogen atmosphere, the obtained second solid particles are subjected to a second sintering treatment at a sintering temperature of 550° C. for 3 hours. After the sintering is completed, a double-layer carbon-coated lithium iron phosphate composite material is obtained.
[0146] The obtained double-layer carbon-coated lithium iron phosphate composite material was placed under a transmission electron microscope for observation. It can be seen that the surface of the lithium iron phosphate is sequentially coated with a first carbon coating layer and a second carbon coating layer, and the degree of graphitization of the first carbon coating layer is significantly higher than that of the second carbon coating layer; and, according to transmission electron microscope observation, the thickness D1 of the first carbon coating layer is 2nm, and the thickness D2 of the second carbon coating layer is 6nm.
[0147] The obtained double-layer carbon-coated lithium iron phosphate composite material was subjected to Raman testing, and the obtained I D / I G It is 1.42.
[0148] The carbon content of the composite material prepared in steps 2 and 5 was tested, and it was found that the total mass of the carbon coating layer was 1.7% of the mass of the double-layer carbon-coated lithium iron phosphate composite material, wherein the mass of the first carbon coating layer accounted for 0.5% of the total mass of the double-layer carbon-coated lithium iron phosphate composite material, and the mass of the second carbon coating layer accounted for 1.2% of the total mass of the double-layer carbon-coated lithium iron phosphate composite material.
[0149] The value calculated according to (I1*C1) / (I2*C2) is (0.95*0.5) / (1.42*1.2)=0.27.
[0150] TEM observation results show that there are 4 carbon layers in the first carbon coating layer.
[0151] According to M1 / (L1 2 *D1*D2) is calculated to be 1.7 / (4 2*2*6)=0.008.
[0152] Comparative Example 1
[0153] This comparative example provides a method for preparing a carbon-coated lithium iron phosphate composite material, comprising the following steps:
[0154] Step 1, dispersing lithium carbonate and iron phosphate in water and ball milling them to obtain a first dispersed slurry after ball milling for 4 hours;
[0155] Step 2, spray drying the first dispersed slurry at a spray drying temperature of 200° C. to obtain first solid particles;
[0156] The first solid particles were subjected to a first sintering treatment in a nitrogen atmosphere. 3 Acetylene gas was introduced at a rate of / h, the temperature in the furnace was controlled at 720°C, and a single-layer carbon-coated lithium iron phosphate composite material was obtained after sintering for 3h.
[0157] Raman testing was performed on lithium iron phosphate coated with a single layer of carbon coating, and I D / I G is 0.85.
[0158] The obtained carbon-coated lithium iron phosphate composite material was placed under a transmission electron microscope for observation. Figure 2 As shown, it can be seen that the surface of lithium iron phosphate is only coated with a single layer of carbon coating. According to transmission electron microscopy observation, the thickness of the carbon coating layer is 3 nm.
[0159] Comparative Example 2
[0160] This comparative example provides a method for preparing a carbon-coated lithium iron phosphate composite material, comprising the following steps:
[0161] Step 1, dispersing lithium carbonate, iron phosphate and glucose in solvent water for mixed ball milling for 6 hours to obtain a mixed material dispersion slurry;
[0162] Step 2, spray drying the mixed material dispersion slurry at a spray drying temperature of 230° C. to obtain solid particles;
[0163] Step 3: In a nitrogen atmosphere, the solid particles are subjected to high-temperature sintering treatment at a temperature of 700° C. After sintering for 4 hours, a carbon-coated lithium iron phosphate composite material is obtained.
[0164] The obtained carbon-coated lithium iron phosphate composite material was subjected to Raman testing, and the obtained I D / I G is 1.53.
[0165] The composite material prepared in step 3 was tested for carbon content, and the mass of the carbon coating layer was 1.45% of the mass of the carbon-coated lithium iron phosphate composite material.
[0166] Comparative Example 3
[0167] This comparative example provides a method for preparing a double-layer carbon-coated lithium iron phosphate composite material, comprising the following steps:
[0168] Step 1, dispersing lithium carbonate, iron phosphate and sucrose in water and ball milling them to obtain a first dispersed slurry after ball milling for 4 hours;
[0169] Step 2, spray drying the first dispersed slurry at a spray drying temperature of 250° C. to obtain first solid particles;
[0170] The first solid particles were subjected to a first sintering treatment in a nitrogen atmosphere, and the temperature in the furnace was controlled to be 720° C. After sintering for 3 hours, lithium iron phosphate coated with a first carbon coating layer was obtained. The lithium iron phosphate coated with the first carbon coating layer was subjected to a Raman test, and I D / I G is 1.52;
[0171] Step 3, crushing the lithium iron phosphate coated with the first carbon coating layer, and crushing the lithium iron phosphate coated with the first carbon coating layer;
[0172] Step 4: Under nitrogen atmosphere, the obtained second solid particles are subjected to a second sintering treatment according to 3.0 m 3 Acetylene gas was introduced at a rate of / h, the sintering temperature was 700°C, and the sintering time was 4h. After the sintering, a double-layer carbon-coated lithium iron phosphate composite material was obtained.
[0173] The obtained double-layer carbon-coated lithium iron phosphate composite material was subjected to Raman testing, and the obtained I D / I G is 1.26.
[0174] The conductivity of the lithium iron phosphate composite materials provided by Examples 1 to 4 and Comparative Examples 1 to 3 was tested by using a method for testing the conductivity of powder by powder tableting. The test results are shown in Table 1.
[0175] The lithium iron phosphate composite material, conductive agent and binder provided in Examples 1 to 4 and Comparative Examples 1 to 3 were dispersed in a solvent N-methylpyrrolidone (NMP) at a ratio of 96.0:1.5:2.5 to obtain a positive electrode active material layer slurry. The positive electrode active material layer slurry was coated on the surface of the positive electrode current collector aluminum foil, and the solvent was dried and rolled to obtain a positive electrode sheet. The compaction density of the positive electrode active material layer was 2.4 g / cm 3The wetting time of the prepared positive electrode plate in the electrolyte was tested. Specifically, the prepared positive electrode plate was placed flat on a clean table, 0.1 mL of electrolyte was taken with a pipette and dripped on the plate. More than 10 points were dripped and the disappearance time of each point was recorded. The average value was the wetting time of the plate. The test results are shown in Table 1.
[0176] The prepared positive electrode sheet was used to prepare a button battery, which was charged to 3.8V at 0.1C constant current and constant voltage, allowed to stand for 5 min, and then discharged to 2.0V at 0.1C constant voltage, allowed to stand for 5 min. The above steps were repeated 5 times, and the capacity and initial efficiency of the button battery were tested. The test results are shown in Table 1.
[0177] The prepared positive electrode sheet was used to prepare a battery, and the DC internal resistance DCR of the battery was tested. The test results are shown in Table 1.
[0178]
[0179] According to the data provided in Table 1, compared with Comparative Examples 1 to 3, under the condition of the same compaction density, the double-layer carbon-coated lithium iron phosphate composite material provided in Examples 1 to 4 of the present application can effectively take into account both the electrical conductivity and the wetting time of the positive electrode plate to the electrolyte, and the DCR of the battery cell is reduced, which helps to improve the rate performance and low temperature performance of the lithium-ion battery including the double-layer carbon-coated lithium iron phosphate composite material.
[0180] According to the data provided in Table 1, in Examples 1 to 4, as the calculated result of (I1*C1) / (I2*C2) increases, the conductivity of the lithium iron phosphate composite material increases and the battery DCR decreases, which helps to improve the rate performance and low temperature performance of the lithium ion battery including the double-layer carbon-coated lithium iron phosphate composite material.
[0181] In summary, the present application provides a double-layer carbon-coated lithium iron phosphate composite material, including lithium iron phosphate and a first carbon coating layer and a second carbon coating layer sequentially coated on the surface of the lithium iron phosphate, and the graphitization degree of the first carbon coating layer is higher than that of the second carbon coating layer, which helps to improve the conductivity of the lithium iron phosphate, and the second carbon coating layer includes amorphous carbon, which has rich organic functional groups that can effectively improve the interface wettability between the electrolyte and the lithium iron phosphate. Therefore, the double-layer carbon-coated lithium iron phosphate composite material provided by the present application helps to improve the rate performance and low temperature performance of the battery.
[0182] In the description of the present application specification, terms such as "inside" and "outside" indicating directions or positional relationships are based on the directions or positional relationships shown in the drawings. This is merely for the convenience of description and does not indicate or imply that the device or component must have a specific orientation, be constructed and operated in a specific orientation. Therefore, it should not be understood as a limitation on the present application.
[0183] In the description of the specification of this application, the description of the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.
[0184] In the description of the present application specification, the terms "first", "second", "third", "fourth", etc. (if any) are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those illustrated or described herein, for example.
[0185] In the description of the present application specification, the terms "include" and "have" and any variations thereof are intended to cover non-exclusive inclusions. For example, a process, method, system, product or apparatus comprising a series of steps or units is not necessarily limited to those steps or units explicitly listed, but may include other steps or units not explicitly listed or inherent to these processes, methods, products or apparatuses.
[0186] In the description of the present application, the term "plurality" refers to two or more.
[0187] In the description of this application specification, the term "and / or" is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the previous and next associated objects are in an "or" relationship; in a formula, the character " / " indicates that the previous and next associated objects are in a "division" relationship.
[0188] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the embodiments of the present application, rather than to limit them. Although the embodiments of the present application have been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. These modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
Claims
1. A double-layer carbon-coated lithium iron phosphate composite material, characterized in that: The composite material includes lithium iron phosphate and a carbon coating layer coated on the surface of the lithium iron phosphate, the carbon coating layer includes a first carbon coating layer and a second carbon coating layer, the first carbon coating layer is coated on the surface of the lithium iron phosphate, and the second carbon coating layer is coated on the surface of the first carbon coating layer away from the lithium iron phosphate, wherein: The first carbon coating layer D / I G Less than the I of the second carbon coating layer D / I G , I D / I G It refers to the peak intensity ratio of the D peak and the G peak in the Raman spectra of the first carbon coating layer and the second carbon coating layer.
2. The lithium iron phosphate composite material according to claim 1, characterized in that: I of lithium iron phosphate composite material coated with a first carbon coating layer D / I G 0.7~0.95; And / or, a lithium iron phosphate composite material coated with a first carbon coating layer and a second carbon coating layer D / I G It is 1.0~1.
3.
3. The lithium iron phosphate composite material according to claim 1, characterized in that: I of lithium iron phosphate composite material coated with a first carbon coating layer D / I G I1, I of the lithium iron phosphate composite material coated with the first carbon coating layer and the second carbon coating layer D / I G The mass of the first carbon coating layer accounts for C1% of the total mass of the double-layer carbon-coated lithium iron phosphate composite material, the mass of the second carbon coating layer accounts for C2% of the double-layer carbon-coated lithium iron phosphate composite material, and (I1*C1) / (I2*C2)≥1.
5.
4. The lithium iron phosphate composite material according to claim 1 or 3, characterized in that: The mass ratio of the first carbon coating layer to the second carbon coating layer is 1:(0.2-0.5).
5. The lithium iron phosphate composite material according to any one of claims 1 to 4, characterized in that: The mass of the carbon coating layer accounts for a percentage of the total mass of the lithium iron phosphate composite material of M1%, the number of carbon layers of the first carbon coating layer is L1, the thickness of the first carbon coating layer is D1, the thickness of the second carbon coating layer is D2, M1 / (L1 2 *D1*D2)≥0.0013.
6. The lithium iron phosphate composite material according to claim 1 or 5, characterized in that: The percentage M1% of the mass of the carbon coating layer to the total mass of the lithium iron phosphate composite material is 1.0% to 3.0%.
7. The lithium iron phosphate composite material according to claim 1 or 5, characterized in that: The number of carbon layers L1 of the first carbon coating layer is 2 to 20 layers.
8. The lithium iron phosphate composite material according to claim 1 or 5, characterized in that: The thickness D1 of the first carbon coating layer is 1-15 nm.
9. The lithium iron phosphate composite material according to claim 1 or 5, characterized in that: The thickness D2 of the second carbon coating layer is 1-15 nm.
10. A method for preparing the lithium iron phosphate composite material according to any one of claims 1 to 9, characterized in that: The steps include: Dispersing a lithium source, a phosphorus source, and an iron source in a solvent and performing ball milling to obtain a first dispersed slurry; The first dispersed slurry is spray-dried, and the obtained first solid particles are subjected to a first sintering treatment; during the first sintering treatment, a first carbon source is introduced to perform chemical vapor deposition to obtain lithium iron phosphate coated with a first carbon coating layer; Dispersing lithium iron phosphate coated with a first carbon coating layer and a second carbon source in a solvent, and mixing them evenly to obtain a second dispersed slurry; The second dispersed slurry is spray-dried, and the obtained second solid particles are subjected to a second sintering treatment to obtain a double-layer carbon-coated lithium iron phosphate composite material.
11. The preparation method according to claim 10, characterized in that: The temperature of the first sintering treatment is 500-900°C and the time is 3-20h; And / or, the temperature of the second sintering treatment is 300-700° C., and the time is 2-15 hours.
12. A pole piece, characterized in that: The invention comprises the double-layer carbon-coated lithium iron phosphate composite material as claimed in any one of claims 1 to 9.
13. A lithium ion battery, characterized in that: Including the pole piece as claimed in claim 12.
14. An electronic device, characterized in that: The driving source or energy storage source of the electronic device includes the lithium-ion battery according to claim 13.
Citation Information
Cited By
Lithium iron phosphate positive electrode material with high cycle stability and preparation method of lithium iron phosphate positive electrode material
CN120998972A
A lithium iron phosphate positive electrode material with high cycle stability and a preparation method thereof
CN120998972B
Composite carbon coated polyanion positive electrode material as well as preparation method and application thereof
CN121439745A
Lithium-ion secondary battery, battery apparatus, electrical apparatus, preparation method for positive electrode active material, and preparation method for positive electrode plate
US12706303B1